THE INSTRUCTIONS OF VOTERS AS A REPRESENTATION OF THE POST-WAR EVERYDAY PROBLEMS OF THE POPULATION OF MOZDOK - E. V. KHUBULOVA; L. Ch. KHABLIEVA (Кавказология, 2021)
Based on the analysis of a wide range of archival sources that are being introduced into scientific circulation for the first time, the article examines the everyday problems of the post-war city of Mozdok. It is noted that the election campaigns were arranged in such a way that it looked like a kind of ritual symbolizing the symbiosis of power and society. At the same time, the election campaigns were the points of contact when the authorities received an objective picture of the relations of the population of the country to the events taking place. The analysis of the instructions of the voters of 1948 and 1953 indicates that they, as a historical source, contain information that allows us to recreate the picture of the everyday life of the post-war provincial society (on the example of Mozdok). The author comes to the conclusion that the party-bureaucratic apparatus used all sorts of communication mechanisms to obtain objective data about the everyday problems of the residents of Mozdok. This information was used for the preparation and implementation of various activities.